Volar Dislocation of the Index, Middle, and Ring Carpometacarpal Joints. Issue 3 (March 2015) - Schaefer, Nathan; Elliott, Devlin; Loveridge, Jeremy
<x xml:space="preserve">Abstract</x> Summary: Dislocation of the index, middle, and ring carpometacarpal joints is an extremely rare injury pattern, with a paucity of published cases. We reviewed the literature and analyzed our own experience to familiarize clinicians with this rare condition through discussion of its clinical presentation, diagnostic considerations, and management. We present the rare case of volar-radial dislocation of the index, middle, and ring carpometacarpal joints in a 61-year-old woman. She underwent a closed reduction with percutaneous Kirschner wire fixation and regained a painless full range of motion after 12 weeks. Dislocation of a carpometacarpal joint is an uncommon injury and can be easily missed. A lateral roentgenogram is essential to accurately identify this injury. Reduction should be achieved as soon as possible, and maintaining reduction with internal fixation is often required due to the acquired instability of the joint. A full return to preinjury status can be expected in most cases.